MENYINGKAP RAGAM TEKS HADIS : (Kajian Hadis tentang Rukyat al-Hilal Riwayat Imam Muslim) - Zainuddin; Mukhlison Efendi (Institut Agama Islam Darul Ulum Kandangan, 2026)
The Qur'an and the Sunnah, as the two primary sources of Islamiclaw, continue to present interpretive challenges that contribute to scholarlydisagreements. One notable example concerns the prophetic traditions (hadith)on ru'yat al-hilal (crescent moon sighting) for determining the beginning of theIslamic lunar month. An examination of Sahih Muslim (Al-Maktabah AlShamilah edition) reveals significant textual variation among the narrations.Eight traditions (Nos. 5, 10–16) either omit the term ru'yah or its lexicalderivatives, or preserve alternative textual formulations, while ten traditions(Nos. 3, 4, 6–9, and 17–20) explicitly employ the term ru'yah and its relatedexpressions. These textual differences correspond to the diversity oftransmission chains (isnad). Ideally, the available narrations should produce nomore than two principal textual forms, reflecting their original transmissionfrom the two primary Companions, Abu Hurairah and Ibn ʿUmar. However,the existing multiplicity of textual variants obscures the originality of thetransmitted wording. Regardless of the long-standing debate over thepermissibility of transmitting hadith by meaning (riwāyah bi al-maʿnā),historical evidence demonstrates that the Prophet's diverse practical precedents(fiʿliyyah), together with differences in narrators' interpretive capacities andtransmission tendencies across various isnads, have contributed to theemergence of multiple textual versions of the same hadith. Consequently, thesetextual variations have generated diverse legal interpretations andunderstandings within the Islamic scholarly tradition